2016
DOI: 10.1016/j.ijer.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-age tutoring in kindergarten and elementary school settings: A systematic review and meta-analysis

Abstract: This systematic review summarizes effects of peer tutoring delivered by non-professional tutors, such as classmates, older children and adult community volunteers, to children between 5 and 11 years old. Inclusion criteria for the review included tutoring studies with a randomized controlled trial design, reliable measures of academic outcomes and a duration of at least 12 weeks.. Searches of electronic databases, previous reviews, and contacts with researchers yielded 11,564 titles. After screening, 15 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 106 publications
(96 reference statements)
0
16
0
1
Order By: Relevance
“…(2018). Regardless of these details, research has shown once again that peer tutoring usually has a positive effect on the academic performance of both the tutors and tutees (Shenderovich et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(2018). Regardless of these details, research has shown once again that peer tutoring usually has a positive effect on the academic performance of both the tutors and tutees (Shenderovich et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Anak mempunyai perspektif yang berbeda ketika melihat karakteristik temannya yang berbeda (Lee & Park, 2009;Özokçu, 2019;Shenderovich, Thurston, & Miller, 2014), dan tidak sedikit perbedaan dari karakteristik temannya menjadi bahan perbincangan antar teman dan ejekan (Isaacs, 2012;H. Kim, 2009).…”
Section: Hasil Dan Pembahasanunclassified
“…Not only attending prep training, BBC is also supplemented by lesson guides and supervisor observing the tutoring session. Thus, this kind of program is characterized into "highly-structured" program [22].…”
Section: A Learning Classroom Language In Prep Trainingmentioning
confidence: 99%
“…They need not to be competent in all areas of English but having competency in classroom language for classroom management and handling activities is fairly specific [16]. Therefore, providing training for student tutors who act as teachers is required [14,22].…”
Section: Introductionmentioning
confidence: 99%